Tumor Mediastinum Anterior (Yolk Sac Tumor) pada Seorang Laki-Laki Dewasa Muda: Sebuah Kasus yang Jarang: [Yolk Sac Tumor in a Young Man: A Rare Case] - Risnawati Risnawati; Laksmi Wulandari (Jurnal Respirasi, 2016)
Background: Primary mediastinal yolk sac tumor is an extremely rare and highly malignant tumors occuring in children and young adult. They are more common in men. The most common symptoms on ptesentation were dyspnea, chest pain, cought, fever, night sweat, or weight loss. Primary mediastinal tumor are considered to have poor prognosis. Case: A 18- year-old man who presented with shorthness of breath, chest pain, fever, night sweat, and generalized weakness. He had no significant surgical, familiy or social history. The chest X-Ray and computed tomographic scan of the chest showed a large anterior mediasti nal mass. The serum level of alpha- fetoprotein and β-HCG was elevated. The histological examination revealed the finding of yolk sac tumor. This supported the diagnosis of yolk sac tumor. The patient received a combination chemotherapy consisting of cisplatin, etoposide and bleomycin every 3 weeks for total of 4 cycles. Conclusions: Primary mediastinal yolk sac tumor is a rare tumor. The diagnosis should be made not only by morphological studies but the also the patients age and the elevation of serum alpha-fetoprotein. In spite of modern chemotherapy, the prognosis of mediastinal yolk sac tumor remains poor.